Asthma Worsenings: Approaches to Prevention and Management from the Asthma Worsenings Working Group. (2008) - Balter, Meyer; Ernst, Pierre; Watson, Wade; Kim, Harold; Cicutto, Lisa; Beauchesne, Marie-France; Cave, Andrew J; Kaplan, Alan; Hogg, Donna; McIvor, Andrew; Smiley, Tom; Rouleau, Michel; et al.
Abstract : Most asthma patients prescribed maintenance asthma therapies still experience periods of asthma worsenings characterized by daytime or nighttime symptoms, or an increased need for rescue medication. In fact, these episodes are highly prevalent even in patients with well-controlled disease. Published literature suggests that asthma worsenings likely represent a window of opportunity during which patients could intervene early to prevent exacerbations or further deterioration of asthma symptoms. However, current evidence suggests that most patients fail to respond or to self-manage appropriately during these periods. To address the issue of asthma worsenings, an interdisciplinary committee of respirologists, allergists, family physicians, pharmacists and certified asthma educators from across Canada developed a practical definition of asthma worsenings and provided approaches to the prevention and management of these episodes based on current literature. To date, combination inhaled corticosteroid/long-acting beta-agonist therapy, particularly single inhaler maintenance and reliever therapy, appears to be an effective strategy for preventing asthma worsenings and exacerbations. Addressing the potential barriers to appropriate patient self-management of asthma worsenings, such as failure to adequately identify and respond to worsenings, low expectations for controlling asthma, low health literacy and poor patient-health care professional communication, are also critical to the successful prevention and management of these episodes. Finally, an interdisciplinary team approach involving patients and their families, certified asthma educators, primary care physicians, pharmacists and specialists is likely to have the greatest impact on the identification, prevention and management of asthma worsenings.